2014
DOI: 10.1155/2014/185272
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Hospital-Acquired Staphylococcus aureus Isolated from Isfahan, Iran

Abstract: Background. Staphylococcus aureus (S. aureus) is one of the most common pathogens that cause hospital- and community-acquired infections in the world. The use of molecular typing methods is essential for determining the origin of the strains, their clonal relations, and also in epidemiological investigations. The purpose of this study was to determine the prevalence of antibiotic resistant S. aureus isolates and using spa, agr, and SCCmec typing to determine the dominant types in Iran. Material and Method. Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
8
5
1
Order By: Relevance
“…The present study showed that the prevalence of resistant strains to methicillin has steadily increased in comparison with a previous study performed in the same hospital (20% vs. 54%) (5,26). Furthermore, a similar prevalence rate (54%) was reported by Moghadami Based on SCCmec typing, MRSA strains are classified into 5 different allotypes, 2 of which have been identified in Asian countries.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The present study showed that the prevalence of resistant strains to methicillin has steadily increased in comparison with a previous study performed in the same hospital (20% vs. 54%) (5,26). Furthermore, a similar prevalence rate (54%) was reported by Moghadami Based on SCCmec typing, MRSA strains are classified into 5 different allotypes, 2 of which have been identified in Asian countries.…”
Section: Discussionsupporting
confidence: 84%
“…Only 2 isolates with SCCmec type IV belonged to HA-MRSA, while SCCmec types I, II, and III were associated with MRSA strains, isolated from hospitalacquired infections (HA-MRSA) (5,14). In the present study, SCCmec typing did not show 100% typeability and had poor 4 Avicenna J Clin Microb Infec.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Gentamycin is an antibiotic used to treat several types of serious infections, especially staphylococcal infections. The resistance rate to gentamicin was 76% in the present study, which is in line with Goudarzi's study (2) yet was higher than those reported by Havaei et al (21) and lower than that those reported by Wang et al (22). The results demonstrated relatively high resistance to kanamycin (84%), amikacin (48%), and tobramycin (46.4%), which is in agreement with earlier rates reported by Ko et al (23), Rashidi Nezhad et al (16) and also a study conducted by Goudarzi et al (2).…”
Section: Discussionsupporting
confidence: 92%
“…However, low gentamycin resistance rates in Chinese and Iranian MRSA isolates have been reported [3,15,47]. All of the MRSA isolates in the present study were MDR which is in relative line with previous reports from Iran [2,14] and Taiwan [38].…”
Section: Discussionsupporting
confidence: 91%